2016
DOI: 10.1002/acr.22681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Adherence to a Treat‐to‐Target Protocol in Recent‐Onset Rheumatoid Arthritis: Reasons for Compliance and Hesitation

Abstract: Objective. To evaluate rheumatologists' adherence to a low Disease Activity Score (DAS)-steered treat-to-target (T2T) strategy in treatment of patients with rheumatoid arthritis (RA) and to assess associated conditions. Methods. Data of the BeSt study were used, a multicenter T2T strategy trial with 10-year followup. During 3 monthly visits, the physician answered questions about satisfaction with level of RA suppression, agreement with the study protocol, and agreement with the DAS. Associations between the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…On the contrary, nonadherence by physicians in strategic clinical trials was partly because of the discrepancy between physician's opinion on a patient's disease activity and the score results. This situation may indeed occur with DAS28 [58], as DAS28 frequently underestimates and sometimes overestimates disease activity, given the high weight of acute phase reactants and tender joint counts in the formula [59]. Thus, the selection of appropriate endpoints and instruments and the adherence to the strategy are key elements of an optimal therapeutic success.…”
Section: Disease Activity and Outcomes Using Treat-to-targetmentioning
confidence: 99%
“…On the contrary, nonadherence by physicians in strategic clinical trials was partly because of the discrepancy between physician's opinion on a patient's disease activity and the score results. This situation may indeed occur with DAS28 [58], as DAS28 frequently underestimates and sometimes overestimates disease activity, given the high weight of acute phase reactants and tender joint counts in the formula [59]. Thus, the selection of appropriate endpoints and instruments and the adherence to the strategy are key elements of an optimal therapeutic success.…”
Section: Disease Activity and Outcomes Using Treat-to-targetmentioning
confidence: 99%
“…The rate of protocol adherence in BeSt study declined over time, from 100% during the first visit up to around 60% of the visits in the final 2 years. The average adherence during 10‐year follow‐up was 79% . In the new Finnish RA Combination Therapy (NEO‐RACo) trial (n = 93), good, intermediate, and low physician adherence were observed in 33.3%, 34.4%, and 32.3% of patients, respectively.…”
Section: Physician Adherence To Treat‐to‐target Strategiesmentioning
confidence: 99%
“…Physician resistance to change their practice toward some aspects of T2T recommendations (especially frequency of disease monitoring and the use of composite disease activity measures to guide treatment decisions) remains an issue . Busy clinical practice, lack of confidence in composite outcome measures, inadequate understanding of the T2T recommendations, and poor physician‐patient communication were also noted as reasons for physician unwillingness to adopt some T2T recommendations . Practical challenges after implementations of the strategy : The reasons for physician nonadherence to T2T strategies are varied, but can be broadly characterized as patient related (eg, resistance to modify therapy when indicated), physician/disease (eg, persistent disease, relying on clinical scenario rather on composite disease activity measures), therapy related (eg, side effects of medicines), and/or as a result of comorbid conditions . In addition, health care system related factors such as awaiting laboratory results or delays to the approval for use of biological DMARDs or other logistic reasons may also play a role .…”
Section: Physician Adherence To Treat‐to‐target Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies evaluating implementation of the T2T approach in trials and in clinical practice have reported the prevalence of therapy adjustment in response to MHDAS, but not the timing . Observational studies in the US have reported rates of therapy adjustment for patients with MHDAS ranging from 43–85% .…”
Section: Introductionmentioning
confidence: 99%